Activ8 me - fitness self-management application - Chua, Chu Yan (2024)
The deliverable of this project is a mobile application project regarding to fitness self-management. Its focus is to design and develop for an integrated fitness and diet application that can comprehensively promote health through a variety of food and exercise regimens. The fitness self-management will address the shortcomings of existing fitness self-management. A BMI calculator will be included to help users concentrate more on their body measurements. Besides, a daily activity report with crucial details will be added. Additionally, the fitness software will be designed to be more user-friendly for female users by considering their menstrual cycle. Software like Android Studio and Firebase will be used in this project. However, for the hardware, more than one Android smartphone and at least one laptop running Windows 11 would be used for the project's development. The programming part will be done in Java language. This project will analyse five existing famous fitness applications under the term Google Fit, MyFitnessPal, Lifesum, Da-fit, and Fitbit to have a better knowledge of health management app. Hence, Agile methodology is adopted in this project to realize the deliverable. The project will go through a few iterations of the requirements, design, and implementation phases while also adding more functionality to the app until the project is accomplished. In brief, the results demonstrate that a mobile application with unified functionality is efficient in giving fitness enthusiasts, and indirectly a larger population that might need to modify their lifestyles for the better, all-inclusive information on exercise and diet.